Training Increases Understanding of Teachers and Parents About Healthy Food for Children with Autism - Mega Iswari; Kasiyati Kasiyati; Zulmiyetri Zulmiyetri; Yarmis Hasan (Universitas Negeri Padang, 2019)
Autism is a developmental disorder in the brain characterized by the appearance of 3 repetitive, restrictive, stereotypical and obsessive behaviors. Even though there is no definite cause for autism, but some parts of the brain such as the amygdala, hippocampus, limbic system, cerebellum and the cerebral cortex experiences developmental histochemical to anatomic disorders. Until now there are no drugs to cure autism. However, if a child is on a food type diet specifically that discipline can really reduce to his autism. Especially for those who have good intelligence, then they are able to follow the level of education to college. This training activity was attended by all teachers in the Mandiri Character School which was attended by parents of students. This activity was considered successful because parents and teachers were enthusiastic in attending this event. Parents have a high curiosity to regulate a balanced diet for autistic children. Parents and teachers feel this activity is very useful in providing educational services for children with autism, because autistic children must follow a diet program to reduce the child's autism. Therefore, managing a balanced diet is very important for the success of the therapy and the learning process. Thus this activity is very beneficial for parents and teachers in providing services for children with autism. It is expected that parents at home can regulate healthy food patterns for autistic children, while teachers in schools can pay attention to the types of foods that autistic children may and may not consume.